Analisa Biaya Terapi Antibiotik Ceftriakson pada Pasien Infeksi Demam Tifoid Rawat Inap Rumah Sakit Tahun 2020 - Anggi Restyana; Fendy Prasetyawan; Yuneka Saristiana; Nisa Azzahra Dentika; Nina Nur Jannah (Universitas Batanghari Jambi, 2022)
Typhoid fever is an infection of the digestive tract caused by Salmonella typhi (Eberthella typhosa) results in inflammation of the small intestine and the lumen of the digestive tract. Ceftriaxone antibiotic treatment costs for hospitalized typhoid illness patients in 2020 were the focus of this investigation. A cross-sectional strategy was used in the study design, which was based on the collecting of medical records and funding records. From October 2021 to December 2021, the trial was conducted at Hospital X. A sample of typhoid patients admitted to the inpatient ward of Hospital X, with BPJS payment status, was used for this study's data collection. For typhoid patients at Jombang Regency X Hospital, the average cost of ceftriaxone antibiotics totaled IDR 1,502,796 per patient.